Stylistics analysis of the short story “My Old Man” by Ernest Hemingway - Siti Ayu Hardiyanti (English Education Journal, 2021)
This study aims to explore the language style of Ernest Hemingway’s short story “The Old Man”. This research describes the stylistic used in the short story. Ernest Hemingway is one of the famous writers of prose and short story. Many people recognize his special works for short stories because Ernest Hemingway has a characteristic that makes him one of the best short story writers in Europe from a young age. My Old Man is the first work known for the lot use of stylistic styles that distinguish this story from Hemingway’s other works. The researcher limits the stylistic only to explore linguistics such as pragmatics and semantics. In addition, the researcher explains the features of stylistic devices which are on simile, poetry, and calque. This study combines 2 methods of analysis, namely textual and stylistic analysis. The results illustrated how Hemingway used stylistic to describe a child as the narrator, where he told in detail the dark experiences of his father in the world of horse racing in a coherent manner. Hemingway combined his imagination with processing language styles in the story.